Association between Mountain Bike and Folding Bicycle Usage with Lower Extremity Pain - David Amadeus Alexander; Darmawati Ayu Indraswari; Raden Mas Soerjo Adji; Sumardi Widodo (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2022)
Background: Lower extremity pain from cycling with wrong technique or without adequate preparation could cause bodily injury and pain. Pain might cause reduced patient’s mobility and quality of life in physical and psychological aspects which results in disruption of sufferers when did their daily activities.Objective: Knowing relationship between uses of mountain bikes and folding bicycles with lower extremity pain.Methods: 65 respondents were involved in research conducted in Semarang online at the respective respondent's and researcher's premises. The study used cross-sectional method to assess relationship between certain types of bicycles uses with lower extremity pain presence and quality. Statistical test used in this study was the Mann-Whitney and Fischer's exact test.Results: There were significant differences in handlebar height, saddle height, and wheel diameter between two groups of respondents (p = 0.032, p = 0.001, p < 0.001). There was insignificant difference between mountain bikes and folding bicycles uses with lower extremity pain presence and quality (p = 0.481, p = 0.599). There was also non-significant correlation and very weak correlation mountain bikes and folding bicycles uses with lower extremity pain presence and quality (p = 0.613, p = 0.603), negative correlation to presence of pain (r = -0.088), and positive correlation to quality of pain (r = 0.066). Location of lower extremity which felt most painful by respondents was knee in both groups.Conclusion: There was insignificant relationship between certain types of bicycles uses with lower extremity pain.